PELESTARIAN ARSITEKTUR LANGGAR DHUWUR MBAH YAI MASTUR LAMONGAN - Hammam Rofiqi Agustapraja (Universitas Islam Lamongan, 2018)
Langgar Dhuwur Mbah Yai Mastur is a lifted small mosque established by Hadratus Syaikh KH. Mastur Asnawi, until now it is still used for the activities of the Tahfidhul - Qur'an Islamic Boarding School, in terms of architecture, this building has different characteristics from the surrounding buildings, namely a simple design in the form of a stage made of wood and roofed with traditional roof (Limasan), so that the existence of meaning Historically this violation has not been eroded by development, so the need for research on architectural preservation with the consideration that this object has fulfilled the requirements of the Cultural Heritage Objects Act No. 11 of 2010, the method used to examine the preservation of architecture is a method of qualitative analysis using an approach with three methods, namely analysis description method, evaluative method and development method. The results of this study indicate that some visual elements of Langgar Dhuwur are still permanent, which can be known through observation on the object of study. Preservation directives for building visual elements are classified into three potential, namely low, medium and high potential, then from the three potential levels, preservation actions will be determined